Corrosion Inhibition of Zn in a 0.5 M HCl Solution by Ailanthus Altissima Extract - Fouda,A. S. (2018)
The inhibiting effect of Ailanthus altissima aqueous extract, as a corrosion inhibitor for Zn in a 0.5 M HCl solution, has been evaluated by weight loss (WL), hydrogen evolution (HE), potentiodynamic polarization (PP), electrochemical impedance spectroscopy (EIS) and electrochemical frequency modulation (EFM) techniques. Obtained results showed that this extract offered good protection against Zn corrosion, and exhibited high inhibition efficiencies. The IE was found to increase with an increasing extract dose. Results revealed that this extract acted as a mixed-type inhibitor, and adsorbed onto the Zn surface following Temkin isotherm. Obtained results were justified from the study of surface morphology.